SPEECH STYLE USED BY SETO MULYADI IN ISLAMIC DA’WAH - Pamungkas, Firdaus Ditya (UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
Speech is a fundamental component of human communication, and it is shaped by a multitude of factors, leading to the emergence of various speech styles. Speech style is a type of communicative style that is determined by an intuitive understanding of the levels of familiarity or intimacy between individuals. These variations in speech style can be influenced by cultural, social, and situational factors, which contribute to the richness and diversity of human communication. This study aimed to explore speech style used by Seto Mulyadi Islamic da’wah in Tarawih sermon at Mosque of Gajah Mada University in 2023. Seto Mulyadi is a child psychologist and was the chairman of National Commission for Child Protection of Indonesia who tends to speak in story telling way. This research used qualitative descriptive method as foundation in conducting research. The research data consists of script of Seto Mulyadi's video speech from Youtube. The data analysis process involves four steps: data collection, data condensation, data display, and conclusion drawing/verification. Based on finding, there are frozen style, formal style, consultative style, and casual style occurred in Seto Mulyadi’s utterances. Formal style is the most occurrence speech style in his speech. Furthermore, the personal background of Seto Mulyadi and the recipients of the message also influence variation of his speech style.